Aspectos clínicos e patológicos da intoxicação espontânea por Senecio spp. em ruminantes no Rio Grande do Sul - Giaretta, Paula Roberta (2014)
During 36 months a study was conducted in beef cattle farms in Rio Grande do Sul, Brazil to survey outbreaks of Senecio spp. poisoning. The first part of this dissertation reports an outbreak of Senecio brasiliensis poisoning in cows where the main clinical sign was photosensitization. Adult cows that were placed during six months in a 205-hectare pasture heavily infested by Senecio brasiliensis were affected in September, 2013. Photosensitization was seen in 83 out 162 cows. Liver biopsy was performed in all cows under risk and three cows were necropsied. Histopathological findings in the liver related to pyrrolizidine alkaloids toxicosis consisted of fibrosis, megalocytosis and biliary ductal proliferation and were present in 119 of the biopsied cows. Six tested cows had increased serum activity of gamma glutamyl transferase. In the second part of this dissertation, a study of an outbreak of seneciosis in sheep in 2014 is reported. Morphological aspects considered important for the establishment of diagnosis in this species were stressed. Ten out of 860 adult sheep with clinical signs of seneciosis died spontaneously and eight sick ewes were euthanized and necropsied. Clinical signs included weight loss, apathy and photosensitization. Four out of seven tested sheep presented increased serum levels of gamma glutamil transferase and two had elevated alkaline phosphatase serum activity. At necropsy, three out of eight ewes presented slightly irregular toughened livers with multifocal nodules, two out of eight ewes had a whitish liver with thickened fibrotic Glisson s capsule partially adhered to the diaphragm, and three out of eight ewes had smooth and grossly normal livers. Histologically, the main hepatic findings that allowed for the establishment of the diagnosis were megalocytosis, proliferation of bile ducts and fibrosis. Spongy degeneration was observed in the brains of all eight necropsied sheep and was more severe at the cerebellar peduncles, mesencephalon, thalamus, and pons. These are suggested as the portions of election to investigate microscopic lesions of hepatic encephalopathy in sheep with chronic seneciosis.